PERANCANGAN ENTERPRISE ARCHITECTURE MENGGUNAKAN THE OPEN GROUP ARCHITECTURE FRAMEWORK (TOGAF) (Studi Kasus: UNIVERSITAS BALE BANDUNG) - Imung Mundirin (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2014)
One of the benefits of enterprise architecture implementation in an organization is to utilize information technology in achieving the vision and mission of an organizations of the business. Enterprise architecture required to design a complete methodology so as to meet all the necessary requirements starting from the initial stage to the final stage. The Open Group Architecture Framework (TOGAF) Architecture Develoment Method (ADM) is a methodology used to analyze the overall Business Architecture. Adapaun architecture supported by TOGAF, among others: Business Architecture, Data Architecture, Application Architecture and Technology Architecture. Enterprise Architecture design is done with the approach of key business processes and supporting business processes. Results of this research is in the form of an architectural model design information systems that support performance improvement of overall information system services.